5-Hydroxyindolacetic Acid (5-HIAA), a Main Metabolite of Serotonin, is Responsible for Complete Freund's Adjuvant-Induced Thermal Hyperalgesia in Mice. Issue 1 (30th March 2011) - Chen, Yong; Palm, Florian; Lesch, Klaus-Peter; Gerlach, Manfred; Moessner, Rainald; Sommer, Claudia
Background: The role of serotonin (5-hydroxytrptamine, 5-HT) in the modulation of pain has been widely studied. Previous work led to the hypothesis that 5-hydroxyindolacetic acid (5-HIAA), a main metabolite of serotonin, might by itself influence pain thresholds. Results: In the present study, we investigated the role of 5-HIAA in inflammatory pain induced by intraplantar injection of complete Freund's adjuvant (CFA) into the hind paw of mice. Wild-type mice were compared to mice deficient of the 5-HT transporter (5-HTT−/− mice) using behavioral tests for hyperalgesia and high-performance liquid chromatography (HPLC) to determine tissue levels of 5-HIAA. Wild-type mice reproducibly developed thermal hyperalgesia and paw edema for 5 days after CFA injection. 5-HTT−/− mice treated with CFA had reduced thermal hyperalgesia on day 1 after CFA injection and normal responses to heat thereafter. The 5-HIAA levels in spinal cord and sciatic nerve as measured with HPLC were lower in 5-HTT−/− mice than in wild-type mice after CFA injection. Pretreatment of wild-type mice with intraperitoneal injection of para-chlorophenylalanine (p-CPA), a serotonin synthesis inhibitor, resulted in depletion of the 5-HIAA content in spinal cord and sciatic nerve and decrease in thermal hyperalgesia in CFA injected mice. The application of exogenous 5-HIAA resulted in potentiation of thermal hyperalgesia induced by CFA in 5-HTT−/− mice and in wild-type mice pretreated with p-CPA, but not in wild-type mice without p-CPA pretreatment. Further, methysergide, a broad-spectrum serotonin receptor antagonist, had no effect on 5-HIAA-induced potentiation of thermal hyperalgesia in CFA-treated wild-type mice. Conclusion: Taken together, the present results suggest that 5-HIAA plays an important role in modulating peripheral thermal hyperalgesia in CFA induced inflammation, probably via a non-serotonin receptor mechanism.